The concept of divinity in Malay cosmology - Abdul Latif Samian, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Malay World has undergone several formative experiences in interacting with nature, the latest of which is influenced mostly by the Islamic civilization. In tandem with these changes, the view the Malays acquired in engaging with the cosmos is fundamentally shaped by their theological belief. In this paper, the author attempts to elucidate their concept of divinity, which is based on their theology, to the extent that it shapes their views about the cosmos.